Acylation of Anisole With Benzoyl Chloride Over Rapidly Synthesized Fly Ash–Based HBEA Zeolite - Ameh, Alechine E.; Musyoka, Nicholas M.; Oyekola, Oluwaseun; Louis, Benoit; Petrik, Leslie F. (Frontiers in Chemistry, 2021)
Stable HBEA zeolite with high surface area and strong acid sites was synthesised from coal fly ash based silica extract via an indirect hydrothermal synthesis. The rapid HBEA hydrothermal crystallisation times of 8, 10 and 12 h were achieved through reduced molar water fraction in the synthesis composition. The HBEA zeolites prepared from fly ash silica extract exhibited well-defined spheroidal-shaped crystal morphology with uniform particle sizes of 192, 190 or 239 nm obtained after 8, 10 or 12 h synthesis time, respectively. High surface area and microporous area of 702, 633, 722 m2/g, were achieved as a function of shorter hydrothermal synthesis durations (10, 12 and 24 h, respectively) compared to 48 or 72 h which resulted in HBEA zeolite with lower surface areas of 538 and 582 m2/g. Likewise, TPD measurements of fly ash based HBEA zeolites revealed the presence of weak and strong acid sites in the zeolite. The sub-micron crystal sizes with well-defined hierarchical porosity of HBEA zeolite enhanced the diffusion of anisole and benzoyl chloride molecules towards the active acid sites and hence showed better conversion and selectivity in acylation products. High conversion of benzoyl chloride with anisole was reached, up to 83% with a 93-96% selectivity towards 4-methoxyacetophenone.